2007
DOI: 10.1088/0022-3727/40/14/008
|View full text |Cite
|
Sign up to set email alerts
|

A double inductively coupled plasma for sterilization of medical devices

Abstract: A double inductively coupled low pressure plasma for sterilization of bio-medical materials is introduced. It is developed for homogeneous treatment of three-dimensional objects. The short treatment times and low temperatures allow the sterilization of heat sensitive materials like ultra-high-molecular-weight-polyethylene or polyvinyl chloride. Using a non-toxic atmosphere reduces the total process time in comparision with common methods. Langmuir probe measurements are presented to show the difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 25 publications
1
112
1
Order By: Relevance
“…A double inductively coupled low-pressure plasma (DICP) source (see Fig. S1 in the supplemental material) (30,31) was used in this study. The stainless steel cylinder of the DICP vessel is enclosed by two quartz glass plates with enclosed copper coils at the top and bottom, which couple a maximum power of 5 kW at 13.56 MHz to the discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A double inductively coupled low-pressure plasma (DICP) source (see Fig. S1 in the supplemental material) (30,31) was used in this study. The stainless steel cylinder of the DICP vessel is enclosed by two quartz glass plates with enclosed copper coils at the top and bottom, which couple a maximum power of 5 kW at 13.56 MHz to the discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, if the system is not operated, a turbo pump is used for evacuating the system below 5 ϫ 10 Ϫ4 Pa for maintaining the cleanliness of the system. The plasma discharge is homogeneous over nearly the entire vessel (30). Several flanges in the vessel allow different optical and electrical analytical devices to be coupled to the vessel for plasma diagnostics.…”
Section: Methodsmentioning
confidence: 99%
“…Figures 1(a)-(d) present SEM images of (a) untreated stacked spore colonies and spores exposed to (b) H 2 O plasma discharge, as well as (c) O 2 , and (d) H 2 , plasma for comparison. Both control gas mixtures have been reported to be effective against bacterial spores when samples are exposed to the active region of the discharge [13,35,36] or to combined radicals ion beams [27]. Only the gas composition was varied during experiments while all other process parameters (power 500 W, pressure 10 Pa and gas flow 10 sccm) were kept constant.…”
Section: Water Vapour Plasma Decontamination Efficiencymentioning
confidence: 99%
“…The cold plasma has been proven to be effective in terms of microbial inactivation and surface decontamination and sterilization [41,42]. Numerous studies showed activity of non-thermal plasma against different Gram-negative and Gram-positive bacteria [13,15,[43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%